Secreted Frizzled-Related Protein 4 (SFRP4) is Elevated in Patients with Diabetes Mellitus - Brix, J. M.; Krzizek, E. C.; Hoebaus, C.; Ludvik, B.; Schernthaner, G.; Schernthaner, G. H. (Hormone and Metabolic Research, 2016)
Recently, SFRP4 was identified as a molecular link between islet inflammation and defective insulin secretion. Gene co-expression analysis detected a molecule associated with type 2 diabetes mellitus (T2D), elevated HbA1c, and reduced insulin secretion in mice as well as in a pilot sample of humans. To our knowledge SFRP4 has never been investigated in patients with different types of diabetes. We included 179 patients: 46 with type 1 diabetes (T1D), 30 age matched healthy controls for patients with T1D (CO-T1D), 55 with T2D, 37 with latent autoimmune diabetes of the adult (LADA) and 30 healthy controls (CO) for patients with T2D and LADA. Apart from anthropometric data, lipids and renal parameters were assessed. SFRP4 levels were measured by a commercial ELISA. Patients with diabetes had significant higher SFRP4 levels than CO: T2D vs. CO: 37.1±26.7 vs. 8.8±3.0 ng/ml, p<0.001; LADA vs. CO: 15.6±6.2 vs. 8.7±3.0 ng/ml, p<0.001; T1D vs. CO-T1D: 24.6±17.9 vs. 16.9±4.5 ng/ml, p=0.011. SFRP4 levels were correlated with age, BMI, HbA1c, HDL-cholesterol, and triglycerides. A multivariate model revealed HDL-cholesterol, triglycerides and BMI as predictors for SFRP4. This is the first study demonstrating that SFRP4 is significantly increased in patients with different types of diabetes suggesting that this protein is generally involved in islet dysfunction and potentially subclinical inflammation irrespective of type of diabetes.
Keywords: SFRP4; type 1 diabetes; type 2 diabetes; LADA diabetes